TRANSFORMASI DIGITAL DALAM MEMBENTUK SIKAP TOLERANSI DAN PEMAHAMAN MULTIKULTURAL SISWA SEKOLAH DASAR MELALUI PENDEKATAN DEEP LEARNING: STUDI LITERATUR KUALITATIF - Yohana R Tagu Pati; Celine Koelima; Maikel Theodorus Sabneno; Merlin E. Selan; Gaudensius J. L. Koten (STKIP Subang, 2026)
The rapid development of digital technology has a significant impact on the lives of elementary school students, including in the formation of social and moral character. However, uncontrolled use of digital media has the potential to reduce students' tolerance, empathy, and multicultural understanding. This study aims to analyze, evaluate, and describe the role of digital transformation in shaping tolerance and multicultural understanding in elementary school students through a deep learning approach. This study uses a qualitative approach with a literature study design. The research subjects were various literature sources consisting of national and international journals, books, scientific articles, and relevant documents related to digital transformation, tolerance, multicultural education, and the deep learning approach. The data collection method was carried out through a literature review using a research instrument in the form of a human instrument assisted by an analysis grid of the study. Data analysis used the Miles and Huberman technique, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that digital transformation integrated with a deep learning approach can increase student learning engagement, creativity, and understanding of the values ​​of tolerance and cultural diversity. The conclusion of this study confirms that digital technology can be a means of strengthening character if used wisely, contextually, and supported by deep learning. The implication of this research is the importance of developing digital learning that is inclusive, interactive, and oriented towards the formation of students' social